2019
DOI: 10.1145/3351422.3351432
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Engineering and Evaluating the Apple Wireless Direct Link Protocol

Abstract: Apple Wireless Direct Link (AWDL) is a proprietary protocol deployed in about 1.4 billion1 end-user devices consisting of Apple's main product families such as Mac, iPhone, iPad, Apple Watch, and Apple TV? effectively all recent Apple devices containing a Wi-Fi chip. Apple does not advertise the protocol but only vaguely refers to it as a "peer-to-peer Wi-Fi" technology [2]. Yet, it empowers popular applications such as AirDrop and AirPlay that transparently use AWDL without the user noticing. We believe that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…However, there is a lack of highly usable approaches to sufficiently protect identification and private information in protocol executions, especially for privacy-concerned parties. A survey [4] showed that about 90% users considered the exposure of device names from wireless network services as a privacy risk, as such exposure may lead to adversarial inference of users' private information such as mobility patterns, profiles, and locations [5], [6], [7], [8]. For instance, in public Wi-Fi, ISP could easily identify a person via the announced device names [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a lack of highly usable approaches to sufficiently protect identification and private information in protocol executions, especially for privacy-concerned parties. A survey [4] showed that about 90% users considered the exposure of device names from wireless network services as a privacy risk, as such exposure may lead to adversarial inference of users' private information such as mobility patterns, profiles, and locations [5], [6], [7], [8]. For instance, in public Wi-Fi, ISP could easily identify a person via the announced device names [9].…”
Section: Introductionmentioning
confidence: 99%
“…Protocol reverse analysis can be divided into two types: binary analysis of protocol implementation [12][13][14][15] and statistic analysis of unknown protocol traffic [16][17][18][19], which are realized by analyzing the program code of the communication entity program and the protocol message field, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The attacker records relevant BTC and BLE packets and their timestamps. This might include public keys for Apple Find My, RP Is from Exposure Notification, and user identifiers [159]. We also assume that the attacker is able to retrieve public information for each of the considered systems.…”
Section: Attacker Model: Abusing Btc+ble Timing Informationmentioning
confidence: 99%
“…These apps can potentially link the BDADDR to any information they have about the user. Recent works [159,160] demonstrated that other BLE-based Apple protocols such as AWDL, AirDrop and Nearby Action can reveal user identifiers such as hostnames, email hashes and phone number hashes. In case of hostname, the study revealed that about 75% of these hostnames contain the user's first or last name or both.…”
Section: Privacy Implications Of the Attackmentioning
confidence: 99%